Making a Hose by Hand (The Story of Rubber, What it Is and What it Does, 1916)
A man making a rubber hose by hand. A book about rubber sourcing, cultivation, processing, and the industry during the late colonial period. Published by a rubber goods company presumably for marketing. The Boston Woven Hose and Rubber Company was founded in 1880.
Keywords: Rubber industry and trade